Water and the environment innovations issues in irrigation and drainage - Pereira, Luis S (Ed.)_; Gowing, John W (Ed.) (London E and F N Spon, 1998)
Inter-Regional Conference "Environment-Water Innovative issues in Irrigation and Drainage(1st 1998 Lisbon,Portugal)organized by the Portuguese National Committee of the International Commission on Irrigation and Drainage. The conference offers a review by
Portugese National committee of the international commission on irrigation and Drainage selected papers of the 1st inter-Regional conference "Environment waters innorative issues in irrigation and drainage" held in Lisbon, Portugal, September 1998
Keywords: Irrigation engineering-Congresses; Drainage-Congresses; Water quality management-Congresses